Integrating Remote Sensing with Ground-based Observations to Quantify the Effects of an Extreme Freeze Event on Black Mangroves (Avicennia germinans) at the Landscape Scale - Melinda Martinez; Michael J. Osland; James B. Grace; Nicholas M. Enwright; Camille L. Stagg; Simen Kaalstad; Gordon H. Anderson; Anna R. Armitage; Just Cebrian; Karen L. Cummins; Richard H. Day; Donna J. Devlin; et al. (Ecosystems, 2024)

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

Spatial and temporal analysis of the risks posed by metal contamination in coastal and marine sediments of Bahrain - E. E. M. Nicolaus; D. L. Maxwell; A. S. Khamis; K. H. Abdulla; R. P. Harrod; M. J. Devlin; B. P. Lyons (Environmental Monitoring and Assessment, 2022)
Nine metals including Al, Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn were analysed from sediment samples collected from 29 stations since 2007 from Bahraini waters. Within this study, it was investigated whether concentrations of these determinants are at concentrations above internationally established Assessment Criteria (AC). The majority of sites were considered not to pose a toxicological risk in terms of metal contamination. Where breaches occurred, they were mainly from historic samples related to Cr, Cu and Ni contamination. A trend assessment revealed that out of 59 significant trends, 36 were downwards and 23 upwards, indicating that some determinants like Al, Zn and Ni are improving strongly across some sites, whilst areas associated with industrial activity still see some increasing trends for Al, Cd, Pb and Zn.

Stoichiometric Modeling of Artificial String Chemistries Reveals Constraints on Metabolic Network Structure - Devlin Moyer; Alan R. Pacheco; David B. Bernstein; Daniel Segrè (Journal of Molecular Evolution, 2021)
Uncovering the general principles that govern the structure of metabolic networks is key to understanding the emergence and evolution of living systems. Artificial chemistries can help illuminate this problem by enabling the exploration of chemical reaction universes that are constrained by general mathematical rules. Here, we focus on artificial chemistries in which strings of characters represent simplified molecules, and string concatenation and splitting represent possible chemical reactions. We developed a novel Python package, ARtificial CHemistry NEtwork Toolbox (ARCHNET), to study string chemistries using tools from the field of stoichiometric constraint-based modeling. In addition to exploring the topological characteristics of different string chemistry networks, we developed a network-pruning algorithm that can generate minimal metabolic networks capable of producing a specified set of biomass precursors from a given assortment of environmental nutrients. We found that the composition of these minimal metabolic networks was influenced more strongly by the metabolites in the biomass reaction than the identities of the environmental nutrients. This finding has important implications for the reconstruction of organismal metabolic networks and could help us better understand the rise and evolution of biochemical organization. More generally, our work provides a bridge between artificial chemistries and stoichiometric modeling, which can help address a broad range of open questions, from the spontaneous emergence of an organized metabolism to the structure of microbial communities.

Genomic variation of an endosymbiotic dinoflagellate ( Symbiodinium ‘fitti’ ) among closely related coral hosts - Hannah G. Reich; Sheila A. Kitchen; Kathryn H. Stankiewicz; Meghann Devlin‐Durante; Nicole D. Fogarty; Iliana B. Baums (Molecular Ecology, 2021)
Mutualisms where hosts are coupled metabolically to their symbionts often exhibit high partner fidelity. Most reef‐building coral species form obligate symbioses with a specific species of photosymbionts, dinoflagellates in the family Symbiodiniaceae, despite needing to acquire symbionts early in their development from environmental sources. Three Caribbean acroporids ( Acropora palmata , A. cervicornis and their F 1 hybrid) are sympatric across much of their range, but often occupy different depth and light habitats. Throughout this range, both species and their hybrid associate with the endosymbiotic dinoflagellate Symbiodinium ‘ fitti ’. Because light (and therefore depth) influences the physiology of dinoflagellates, we investigated whether S . ‘ fitti ’ populations from each host taxon were differentiated genetically. Single nucleotide polymorphisms (SNPs) among S . ‘ fitti ’ strains were identified by aligning shallow metagenomic sequences of acroporid colonies sampled from across the Caribbean to a ~600‐Mb draft assembly of the S . ‘ fitti ’ genome (from the CFL14120 A. cervicornis metagenome). Phylogenomic and multivariate analyses revealed that genomic variation among S . ‘ fitti ’ strains partitioned to each host taxon rather than by biogeographical origin. This is particularly noteworthy because the hybrid has a sparse fossil record and may be of relatively recent origin. A subset (37.6%) of the SNPs putatively under selection were nonsynonymous mutations predicted to alter protein efficiency. Differences in genomic variation of S . ‘ fitti ’ strains from each host taxon may reflect the unique selection pressures created by the microenvironments associated with each host. The nonrandom sorting among S . ‘ fitti ’ strains to different hosts could be the basis for lineage diversification via disruptive selection, leading to ecological specialization and ultimately speciation.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Velocity Curvature Index: a Novel Diagnostic Biomarker for Large Vessel Occlusion - Samuel G. Thorpe; Corey M. Thibeault; Seth J. Wilk; Michael O’Brien; Nicolas Canac; Mina Ranjbaran; Christian Devlin; Thomas Devlin; Robert B. Hamilton (Translational Stroke Research, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Extensive transcriptional variation poses a challenge to thermal stress biomarker development for endangered corals - John Everett Parkinson; Erich Bartels; Meghann K. Devlin‐Durante; Caitlin Lustic; Ken Nedimyer; Stephanie Schopmeyer; Diego Lirman; Todd C. LaJeunesse; Iliana B. Baums (Molecular Ecology, 2018)
As climate changes, sea surface temperature anomalies that negatively impact coral reef organisms continue to increase in frequency and intensity. Yet, despite widespread coral mortality, genetic diversity remains high even in those coral species listed as threatened. While this is good news in many ways, it presents a challenge for the development of biomarkers that can identify resilient or vulnerable genotypes. Taking advantage of three coral restoration nurseries in Florida that serve as long‐term common garden experiments, we exposed over 30 genetically distinct Acropora cervicornis colonies to hot and cold temperature shocks seasonally and measured pooled gene expression responses using RNA seq. Targeting a subset of 20 genes, we designed a high‐throughput qPCR array to quantify expression in all individuals separately under each treatment with the goal of identifying predictive and/or diagnostic thermal stress biomarkers. We observed extensive transcriptional variation in the population, suggesting abundant raw material is available for adaptation via natural selection. However, this high variation made it difficult to correlate gene expression changes with colony performance metrics such as growth, mortality and bleaching susceptibility. Nevertheless, we identified several promising diagnostic biomarkers for acute thermal stress that may improve coral restoration and climate change mitigation efforts in the future.

Age and intraspecific diversity of resilient Acropora communities in Belize - Adele Irwin; Lisa Greer; Robert Humston; Meghann Devlin-Durante; Paul Cabe; Halard Lescinsky; Karl Wirth; H. Allen Curran; Iliana B. Baums (Coral Reefs, 2017)

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)

Ultrafine Particulate Matter Increases Cardiac Ischemia/Reperfusion Injury via Mitochondrial Permeability Transition Pore - Nathan A. Holland; Chad R. Fraiser; Ruben C. Sloan; Robert B. Devlin; David A. Brown; Christopher J. Wingard (Cardiovascular Toxicology, 2017)

Behaviour of growth hormone transgenic coho salmon O ncorhynchus kisutch in marine mesocosms assessed by acoustic tag telemetry - T. Hollo; B. M. Watson; S.V. Johnston; R. H. Devlin (Journal of Fish Biology, 2017)
Underwater acoustic tag telemetry was used to assess behavioural differences between juvenile wild‐type ( i.e. non‐transgenic, NT ) and growth hormone ( GH ) transgenic (T) coho salmon Oncorhynchus kisutch in a contained simulated ocean environment. T O. kisutch were found across days to maintain higher baseline swimming speeds than NT O. kisutch and differences in response to feeding were detected between T and NT genotypes. This is the first study to assess behaviour of GH transgenic salmonids in a marine environment and has relevance for assessing whether behavioural effects of GH overexpression seen in freshwater environments can be extrapolated to oceanic phases of the life cycle.

Infanticide in a jaguar (Panthera onca) population—does the provision of livestock carcasses increase the risk? - Fernando R. Tortato; Allison L. Devlin; Rafael Hoogesteijn; Joares A. May Júnior; Jacqueline L. Frair; Peter G. Crawshaw; Thiago J. Izzo; Howard B. Quigley (acta ethologica, 2017)

How old are you? Genet age estimates in a clonal animal - M. K. Devlin‐Durante; M. W. Miller; W. F. Precht; I. B. Baums (Molecular Ecology, 2016)
Foundation species such as redwoods, seagrasses and corals are often long‐lived and clonal. Genets may consist of hundreds of members (ramets) and originated hundreds to thousands of years ago. As climate change and other stressors exert selection pressure on species, the demography of populations changes. Yet, because size does not indicate age in clonal organisms, demographic models are missing data necessary to predict the resilience of many foundation species. Here, we correlate somatic mutations with genet age of corals and provide the first, preliminary estimates of genet age in a colonial animal. We observed somatic mutations at five microsatellite loci in rangewide samples of the endangered coral, Acropora palmata ( n = 3352). Colonies harboured 342 unique mutations in 147 genets. Genet age ranged from 30 to 838 years assuming a mutation rate of 1.195 −04 per locus per year based on colony growth rates and 236 to 6500 years assuming a mutation rate of 1.542 −05 per locus per year based on sea level changes to habitat availability. Long‐lived A. palmata genets imply a large capacity to tolerate past environmental change, and yet recent mass mortality events in A. palmata suggest that capacity is now being frequently exceeded.

Marginal coral populations: the densest known aggregation of Pocillopora in the GalÃ¡pagos Archipelago is of asexual origin - Iliana B. Baums; Meghann Devlin-Durante; Beatrice A. A. Laing; Joshua Feingold; Tyler Smith; Andrew Bruckner; Joao Monteiro (Frontiers in Marine Science, 2014)

New insights into the dynamics between reef corals and their associated dinoflagellate endosymbionts from population genetic studies - Iliana B. Baums; Meghann K. Devlin‐Durante; Todd C. LaJeunesse (Molecular Ecology, 2014)
The mutualistic symbioses between reef‐building corals and micro‐algae form the basis of coral reef ecosystems, yet recent environmental changes threaten their survival. Diversity in host‐symbiont pairings on the sub‐species level could be an unrecognized source of functional variation in response to stress. The C aribbean elkhorn coral, A cropora palmata , associates predominantly with one symbiont species ( S ymbiodinium ‘ fitti ’), facilitating investigations of individual‐level (genotype) interactions. Individual genotypes of both host and symbiont were resolved across the entire species’ range. Most colonies of a particular animal genotype were dominated by one symbiont genotype (or strain) that may persist in the host for decades or more. While S ymbiodinium are primarily clonal, the occurrence of recombinant genotypes indicates sexual recombination is the source of this genetic variation, and some evidence suggests this happens within the host. When these data are examined at spatial scales spanning the entire distribution of A . palmata , gene flow among animal populations was an order of magnitude greater than among populations of the symbiont. This suggests that independent micro‐evolutionary processes created dissimilar population genetic structures between host and symbiont. The lower effective dispersal exhibited by the dinoflagellate raises questions regarding the extent to which populations of host and symbiont can co‐evolve during times of rapid and substantial climate change. However, these findings also support a growing body of evidence, suggesting that genotype‐by‐genotype interactions may provide significant physiological variation, influencing the adaptive potential of symbiotic reef corals to severe selection.

Potential for large‐bodied zooplankton and dreissenids to alter the productivity and autotrophic structure of lakes - Scott N. Higgins; B. Althouse; S. P. Devlin; Y. Vadeboncoeur; M. J. Vander Zanden (Ecology, 2014)
While limnological studies have emphasized the importance of grazers on algal biomass and primary production in pelagic habitats, few studies have examined their potential role in altering total ecosystem primary production and it's partitioning between pelagic and benthic habitats. We modified an existing ecosystem production model to include biotic feedbacks associated with two groups of large‐bodied grazers of phytoplankton (large‐bodied zooplankton and dreissenid mussels) and estimated their effects on total ecosystem production (TEP), and the partitioning of TEP between phytoplankton and periphyton (autotrophic structure) across large gradients in lake size and total phosphorus (TP) concentration. Model results indicated that these filter feeders were capable of reducing whole‐lake phytoplankton production by 20–70%, and increasing whole‐lake benthic production between 0% and 600%. Grazer effects on TEP were constrained by lake size, trophic status, and potential feedbacks between grazing and maximum rates of benthic photosynthesis (BP MAX ). In small (mean depth Z¯ 2 ) lakes, both large‐bodied zooplankton and dreissenids were capable of increasing the benthic fraction (Bf) by 10–50% of TEP. Small lakes were also the only systems where TEP had the potential to increase in the presence of large‐bodied grazers, but such increases only occurred if grazer‐induced changes in water clarity, macrophyte coverage, or nutrient availability stimulated specific growth rates of periphyton. In other scenarios, TEP declined by a maximum of 50%. In very large lakes ( Z¯ > 100 m), Bf was minor (

Genotypic variation influences reproductive success and thermal stress tolerance in the reef building coral, Acropora palmata - I. B. Baums; M. K. Devlin-Durante; N. R. Polato; D. Xu; S. Giri; N. S. Altman; D. Ruiz; J. E. Parkinson; J. N. Boulay (Coral Reefs, 2013)

Air pollution and health: emerging information on susceptible populations - Marie S. O’Neill; Carrie V. Breton; Robert B. Devlin; Mark J. Utell (Air Quality, Atmosphere & Health, 2012)

Microsatellite loci for Symbiodinium A3 (S. fitti) a common algal symbiont among Caribbean Acropora (stony corals) and Indo-Pacific giant clams (Tridacna) - Jorge H. Pinzón; Meghann K. Devlin-Durante; Michele X. Weber; Iliana B. Baums; Todd C. LaJeunesse (Conservation Genetics Resources, 2011)

Host population genetic structure and zooxanthellae diversity of two reef-building coral species along the Florida Reef Tract and wider Caribbean - I. B. Baums; M. E. Johnson; M. K. Devlin-Durante; M. W. Miller (Coral Reefs, 2010)

Differential Cardiopulmonary Effects of Size-Fractionated Ambient Particulate Matter in Mice - Haiyan Tong; Wan-Yun Cheng; James M. Samet; M. Ian Gilmour; Robert B. Devlin (Cardiovascular Toxicology, 2010)

Wild Atlantic salmon Salmo salar L. strains have greater growth potential than a domesticated strain selected for fast growth - L. Neregård; L. Sundt‐Hansen; K. Hindar; S. Einum; J. I. Johnsson; R. H. Devlin; I. A. Fleming; B. Th. Björnsson (Journal of Fish Biology, 2008)
A study was undertaken to examine the responses of three Atlantic salmon Salmo salar strains to growth hormone (GH) treatment. A positive growth response to sustained‐release GH implants was found in two wild strains (Namsen and Imsa) as well as one domesticated strain (AquaGen). The data revealed that the growth‐selected AquaGen strain has further growth potential, however, a stronger growth response was observed in the wild strains which outgrew the domesticated strain after GH treatment. These observations suggest that some growth potential may have been lost during the selection for rapid growth in the AquaGen strain. In September, the parr were GH implanted and in December sampled for plasma GH and insulin‐like growth factor I (IGF‐I) levels, liver, muscle and gill GH receptor, IGF‐I mRNA levels, gill Na + ,K + ‐ATPase activity, muscle and liver lipid content and body silvering. Low temperature and seasonal growth cessation probably explains the relatively limited GH effects found. Body silvering in all strains was positively correlated to size. GH increased IGF‐I plasma levels in the Namsen strain inspite of liver IGF‐I mRNA levels being lower in GH‐treated fish.

Genome-wide distribution of linkage disequilibrium in the population of Palau and its implications for gene flow in Remote Oceania - B. Devlin; Kathryn Roeder; Caleb Otto; Seba Tiobech; W. Byerley (Human Genetics, 2001)

Repositioning the hereditary paraganglioma critical region on chromosome band 11q23 - B. E. Baysal; E. M. van Schothorst; Joan E. Farr; P. Grashof; David Myssiorek; Wendy S. Rubinstein; Peter Taschner; Cees J. Cornelisse; B. Devlin; Peter Devilee; C. W. Richard III. (Human Genetics, 1999)

In Vitro Toxicity of Methyl Mercury to Fathead Minnow Cells - E. W. Devlin; B. Clary (Bulletin of Environmental Contamination and Toxicology, 1998)

Adrenocortical activity with repeated administration of one-daily inhaled fluticasone propionate and budesonide in asthmatic adults - A. M. Wilson; D. J. Clark; M. M. Devlin; L. C. McFarlane; B. J. Lipworth (European Journal of Clinical Pharmacology, 1998)

Lack of direct immunosuppressive effects of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) on human peripheral blood lymphocyte subsets in vitro - Dagmar S. Lang; Susannne Becker; George C. Clark; Robert B. Devlin; Hillel S. Koren (Archives of Toxicology, 1994)